Clinical Pharmacokinetics of IPX066: Evaluation of Dose Proportionality and Effect of Food in Healthy Volunteers. Issue 1 (January 2016) - Yao, Hsuan-Ming; Hsu, Ann; Gupta, Suneel; Modi, Nishit B.
Abstract : Objectives: IPX066 is an oral, extended-release capsule formulation of carbidopa-levodopa (CD-LD) available in 4 strengths. The goals of this investigation were to assess the dose proportionality of IPX066 and to study the effects of a high-fat, high-calorie meal and of sprinkling the capsule contents on applesauce on the pharmacokinetics of IPX066 in healthy volunteers. Methods: Three open-label studies were conducted. In the first study, subjects received 1 capsule of each IPX066 strength (23.75–95, 36.25–145, 48.75–195, and 61.25–245 mg of CD-LD). In the second study, subjects received 1 and 2 capsules of IPX066 245-mg LD under fasting conditions. In the third study, subjects received 2 capsules of IPX066 245-mg LD under 3 conditions: fasting; following a high-fat, high-calorie breakfast; and with the capsule contents sprinkled on applesauce under fasting conditions. Results: Peak plasma concentrations ( C max ) and systemic exposure ( AUC t, AUC inf ) for LD and CD increased dose-proportionally over the range of the IPX066 capsule strengths. Comparison of 1 and 2 IPX066 245-mg LD capsules showed dose-proportional pharmacokinetics for C max and AUC t . Sprinkling the capsule contents on applesauce did not affect the pharmacokinetics. A high-fat, high-calorie meal delayed the initial increase in LD concentration by approximately 1 to 2 hours, reduced C max by 21%, and increased AUC inf by 13% compared with the fasted state. Conclusions: IPX066 shows dose-proportional pharmacokinetics. Sprinkling the capsule contents on applesauce does not affect the pharmacokinetics; a high-fat, high-calorie meal delayed absorption by 1 to 2 hours, slightly reduced C max, and slightly increased extent of absorption.